Tinjauan Fikih Ekonomi Terhadap Pengupahan Bajak Sawah di Nagari Padang Laweh Malalo Kecamatan Batipuah Selatan Kabupaten Tanah Datar - Rizki Fadli; Zainuddin Zainuddin (JURNAL HUKUM EKONOMI SYARIAH, 2020)
This article discusses the payment of rice plow from the perspective of Economic Jurisprudence in Nagari Padang Laweh Malalo, Kecamatan Batipuah Selatan, Kabupaten Tanah Datar. The problem is that there has been a change in the tradition of plowing rice fields from using cattle to using tractor engines. These changes also bring changes to the practice of plowing, the efficiency of time, costs, and how wages are calculated. In connection with this the question arises how the review of Economic Jurisprudence on wage plows in Nagari Padang Laweh Malalo Kecamatan Batipuah Selatan Kabupaten Tanah Datar? The type of research I use is library research with a qualitative descriptive approach. The data that the author gets is through interviews. Data sources are farmers who have rice fields or plowsmen. Data is processed by classifying or categorizing the data and analyzed with the theory of Economic Jurisprudence. This study found that the Review of Economic Jurisprudence on wage plows in Nagari Padang Laweh Malalo, Kecamatan Batipuah Selatan, Kabupaten Tanah Datar may be permissible (mubah) due to the addition of wages requested by the plowman to use the machine in accordance with the work produced and in accordance with the Qur'an.